2024
DOI: 10.3390/land13030278
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Spatiotemporal Characteristics and Identifying Influential Factors of Ecosystem Fragmentation in Karst Landscapes: A Comprehensive Analytical Framework

Xiaopiao Wu,
Zhongfa Zhou,
Meng Zhu
et al.

Abstract: Guanling-Zhenfeng County, a microcosm of the ecologically fragile karst area in southwest China, experiences rapid population growth and urban expansion which intensifies land use transformation and ecological landscape fragmentation. Exploring the spatiotemporal characteristics of landscape fragmentation and its causes in Guanling-Zhenfeng County is of great significance in maintaining the stability of the ecosystem and ecological protection in karst areas. In this study, a comprehensive landscape fragmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Given the complex spatial heterogeneity inherent in natural and social systems, drivers exert differing effects on landscape patterns depending on their geographical locations [43,60]. Wu et al found that the distribution of each landscape index had obvious spatial differentiation [61]. Thus, accounting for the spatial heterogeneity of driving mechanisms is crucial for a more accurate depiction of these mechanisms across diverse geographical contexts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the complex spatial heterogeneity inherent in natural and social systems, drivers exert differing effects on landscape patterns depending on their geographical locations [43,60]. Wu et al found that the distribution of each landscape index had obvious spatial differentiation [61]. Thus, accounting for the spatial heterogeneity of driving mechanisms is crucial for a more accurate depiction of these mechanisms across diverse geographical contexts.…”
Section: Introductionmentioning
confidence: 99%
“…However, the impact of these two factor types on landscape patterns is not isolated; rather, they interact synergistically. Wu et al, found that there was a significant interaction enhancement effect between natural and social factors in influencing landscape fragmentation [61]. Nie et al, found the digital elevation model (DEM) and GDP to be the main drivers of landscape patterns using Geodetectors [8].…”
Section: Introductionmentioning
confidence: 99%